Human In Vivo Corona: The Human In Vivo Biomolecule Corona onto PEGylated Liposomes: A Proof‐of‐Concept Clinical Study (Adv. Mater. 4/2019). Issue 4 (22nd January 2019) - Hadjidemetriou, Marilena; McAdam, Sarah; Garner, Grace; Thackeray, Chelsey; Knight, David; Smith, Duncan; Al‐Ahmady, Zahraa; Mazza, Mariarosa; Rogan, Jane; Clamp, Andrew; Kostarelos, Kostas
Abstract : Experimental evidence that a biomolecule corona self‐assembles around clinically used nanoparticles in humans while in their blood circulation is presented by Kostas Kostarelos and co‐workers in article number1803335 . The successful recovery and purification of corona‐coated lipid bilayer vesicles (liposomes) from the blood circulation of ovarian carcinoma patients allows the proteomic analysis of the human in vivo protein corona. This work provides a technology springboard to allow clinical exploitation of protein‐corona fingerprinting as a novel tool to comprehensively analyze the blood circulation proteome.